Pirate pandemonium - Strong, Jeremy; Brown, Judy, illus (London : Puffin, 1997)
Miss Pandemonium and her unruly class clash with Miss Earwigger, the deputy head of Witts End Primary School.
Keywords: Elementary schools -- Juvenile literature; School dicipline -- Fiction